Aryl substitution of pentacenes - Waterloo, Andreas; Sale, Anna Chiara; Lehnherr, Dan; Hampel, Frank; Tykwinski, Rik (Beilstein Journal of Organic Chemistry, 2014)
A series of 11 new pentacene derivatives has been synthesized, with unsymmetrical substitution based on a trialkylsilylethynyl group at the 6-position and various aryl groups appended to the 13-position. The electronic and physical properties of the new pentacene chromophores have been analyzed by UV-vis spectroscopy (solution and thin films), thermoanalytical methods (DSC and TGA), cyclic voltammetry, as well as X-ray crystallography (for 8 derivatives). X-ray crystallography has been specifically used to study the influence of unsymmetrical substitution on the solid-state packing of the pentacene derivatives. The obtained results add to our ability to better predict substitution patterns that might be helpful for designing new semiconductors for use in solid-state devices.
EAM Import::2019-03-13

A Series of Pyrene-Substituted Silicon Phthalocyanines as Near-IR Sensitizers in Organic Ternary Solar Cells - Ke, Lili; Min, Jie; Adam, Matthias; Gasparini, Nicola; Hou, Yi; Perea, Jose Dario; Chen, Wei; Zhang, Hong; Fladischer, Stefanie; Sale, Anna Chiara; Spiecker, Erdmann; Tykwinski, Rik; et al. (Advanced Energy Materials, 2016)
An attractive method to broaden the absorption bandwidth of polymer/fullerene-based bulk heterojunction (BHJ) solar cells is to blend near infrared (near-IR) sensitizers into the host system. Axial substitution of silicon phthalocyanines (Pcs) opens a possibility to modify the chemical, thermodynamic, electronic, and optical properties. Different axial substitutions are already designed to modify the thermodynamic properties of Pcs, but the impact of extending the π-conjugation of the axial ligand on the opto-electronic properties, as a function of the length of the alkyl spacer, has not been investigated yet. For this purpose, a novel series of pyrene-substituted silicon phthalocyanines (SiPc-Pys) with varying lengths of alkyl chain tethers are synthesized. The UV-vis and external quantum efficiency (EQE) results exhibit an efficient near IR sensitization up to 800 nm, clearly establishing the impact of the pyrene substitution. This yields an increase of over 20% in the short circuit current density (J ) and over 50% in the power conversion efficiency (PCE) for the dye-sensitized ternary device. Charge generation, transport properties, and microstructure are studied using different advanced technologies. Remarkably, these results provide guidance for the diverse and judicious selection of dye sensitizers to overcome the absorption limitation and achieve high efficiency ternary solar cells.
Keywords: Absorption limitations; Charge transport; Near-IR sensitizers; Silicon phthalocyanine; Ternary solar cells

Diels-Alder Cycloaddition of Tetraphenylcyclopentadienone and 1,3,5-Hexatriynes - Sale, Anna Chiara; Murray, Adrian H.; Prenzel, Dominik; Hampel, Frank; De Luca, Lidia; Tykwinski, Rik (European Journal of Organic Chemistry, 2016)
Diels–Alder cycloaddition reactions of 1,3,5-hexatriynes with tetraphenylcyclopentadienone have been performed, and mainly gave 1,2-diethynyl-3,4,5,6-tetraphenylbenzene derivatives as products. The Diels–Alder reactions were optimized under conventional heating and microwave irradiation conditions, and showed good selectivity towards the central carbon–carbon triple bond of the triyne. Empirical evidence suggests that the selectivity of the reaction is governed predominantly by the steric demands of the end-groups of the triyne. Several of the Diels–Alder products could be further elaborated by a sequence of desilylation and oxidative homocoupling to provide dimeric products. The homocoupling reaction was optimized by Pd catalysis. The X-ray crystallographic analysis of two derivatives is reported.
EAM Import::2019-03-13

N-Heterotriangulene chromophores with 4-pyridyl anchors for dye-sensitized solar cells - Meinhardt, Ute; Lodermeyer, Fabian; Schaub, Tobias; Kunzmann, Andreas; Dral, Pavlo O.; Sale, Anna Chiara; Hampel, Frank; Guldi, Dirk Michael; Costa, Ruben Dario; Kivala, Milan (RSC Advances, 2016)
A series of dimethylmethylene-bridged N-heterotriangulenes decorated with one, two, and three electron-withdrawing 4-pyridyls were synthesized. Their photophysical and electrochemical characteristics were examined and their successful application in n-type TiO2- and ZnO-based dye-sensitized solar cells demonstrated the ability of the 4-pyridyl moiety to act as an anchor.
EAM Import::2019-03-12